A Study on Men's Violence and Domestic Violence Descriptions - TUNA UYSAL, Meyrem; TAN EREN, Gizem (Journal of History Culture and Art Research, 2020)
The roles of socially constructed "masculinity" and the fact that the social structure is decisive in the acceptance of these roles lead to the legitimacy of violence and the relationship between men and violence according to society. This study aims to address the meanings imposed on masculinity on the axis of violence and domestic violence and men’s regarding violence and domestic violence within the framework of these meanings. In this respect, the relationship between masculinity and violence, which are socially constructed, is discussed in the study based on the narratives of men about violence. Therefore, the study is important for addressing men’s perception of violence and domestic violence, the testimony of violence, the way they define the types of domestic violence, and the proposals for solutions to violence. In this context, in-depth interviews were conducted with eighteen (18) male participants selected through incidental sample. Thus, thoughts of men about violence and domestic violence were wanted to be understood. As a result of the study, it was observed that the perception of violence and their assessments of domestic violence are similar by men with different socio-demographic characteristics. Accordingly, it has been determined that physical violence stands out among the types of violence that men practice, witness or expose.